IDENTIFIKASI BEBERAPA SIFAT KIMIA TANAH GAMBUT PADA KEBUN KELAPA SAWIT RAKYAT DI DESA RASAU JAYA II KABUPATEN KUBU RAYA - Nafa A Permatasari; Denah Suswati; Feira Budiarsyah Arief; Asrifin Aspan Aspan; Asmahan Akhmad (Universitas Muhammadiyah Purwokerto, 2021)
This study identifies the availability of macronutrients N, P, K, Ca, Mg in peat soil and fertilizersuggestions in the management of smallholder oil palm plantations in Rasau Jaya II Village, KubuRaya Regency. This research method is a field survey, where soil samples are taken at depth of 0-30cm and analyzed in the laboratory. The results showed the chemical properties of the soil with thefollowing criteria: very acidic soil reaction (pH); N-total, phosphorus, C-organic, Cation ExchangeCapacity is very high; K-dd low to moderate; low to moderate Ca; Mg is moderate to high andBase Saturation is very low.